2022
DOI: 10.1186/s13643-022-01995-4
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health and cancer screening implementation and outcomes in the USA: a systematic review protocol

Abstract: Background Improving the delivery, uptake, and implementation of cancer screening to meet evidence-based recommendations is needed to reduce persistent cancer health disparities in the USA. Current national public health targets emphasize the role of social determinants of health (SDOH) on cancer screening. However, there remains a need to explicate these linkages, toward the goal of identifying and implementing effective interventions that target and address SDOH to reduce inequities in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…9 Social determinants of health, which are "the conditions in which people live, learn, work, play, worship and age," also have been shown to play a role in access to health maintenance screening for Black women. [35][36][37][38] The type of health insurance coverage has previously been shown to be associated with receipt of preventive health services. 39,40 -3107 (30%).…”
Section: Discussionmentioning
confidence: 99%
“…9 Social determinants of health, which are "the conditions in which people live, learn, work, play, worship and age," also have been shown to play a role in access to health maintenance screening for Black women. [35][36][37][38] The type of health insurance coverage has previously been shown to be associated with receipt of preventive health services. 39,40 -3107 (30%).…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA checklist is available in Supporting Methods File . Our review methods are reported in detail in a previously published protocol 14 …”
Section: Methodsmentioning
confidence: 99%
“…We collaborated with a research librarian and experts in cancer control research to develop the search strategy 14 . Search strings included terms for cancer site, screening test, and SDOH, and US search strategies included limiters, with some variation by database: English language, publication years 2010–2021, human studies, adult studies, US studies, and journal articles or review articles (the latter to facilitate reference hand searching).…”
Section: Methodsmentioning
confidence: 99%
“…Literature reviews from the oral health field may be good resources for hypothesis generation and theory development, including reviews of social determinants of paediatric 32 and adult oral health 33 and disparities in oral health care 34 . Reviews from outside the oral health field may be useful for theory generation too, including related topics such as the social consequences of chronic pain, 35 ageing and caregiving 36 and an in‐progress review of social determinants of cancer screening 37 …”
mentioning
confidence: 99%
“…34 Reviews from outside the oral health field may be useful for theory generation too, including related topics such as the social consequences of chronic pain, 35 ageing and caregiving 36 and an in-progress review of social determinants of cancer screening. 37 For those seeking practical guidance or resources to conduct theory-based research, several relevant initiatives are good sources of such information (e.g. National Institutes of Health Science of Behavior Change Common Fund Program, 38 University College London Human Behaviour-Change Project 39 ).…”
mentioning
confidence: 99%